Intersegment Recombination During Influenza A Virus Replication Gives Rise to a Novel Class of Defective Viral Genomes - Soraya Anisi; George Noble; Rory Williams; Jack Hales; Hannah E. Bridgewater; Andrew Easton; William Collier; Phillip Gould (Viruses, 2025)
Influenza A virus (IAV) is a highly diverse pathogen with genetic variability primarily driven by mutation and reassortment. Using next-generation sequencing (NGS), we characterised defective viral genomes (DVGs) generated during the serial passaging of influenza A/Puerto Rico/8/1934 (H1N1) virus in embryonated chicken eggs. Deletions were the most abundant DVG type, predominantly accumulating in the polymerase-encoding segments. Notably, we identified and validated a novel class of multisegment DVGs arising from intersegment recombination events, providing evidence that the IAV RNA polymerase can detach from one genomic template and resume synthesis on another. Multisegment recombination primarily involved segments 1–3 but also occurred between other segment pairings. In specific lineages, certain multisegment DVGs reached high frequencies and persisted through multiple passages, suggesting they are not transient by-products of recombination but may possess features that support stable maintenance. Furthermore, multisegment DVGs were shown to be encapsidated within virions, similar to deletion DVGs. The observation of recombination between segments with limited sequence homology underscores the potential for complex recombination to expand IAV genetic diversity. These findings suggest recombination-driven DVGs represent a previously underappreciated mechanism in influenza virus evolution.